Comparison of pancreatic lipase inhibitory isoflavonoids from unripe and ripe fruits of Cudrania tricuspidata. - Yang Hee Jo; Seon Beom Kim; Qing Liu; Seon-Gil Do; Bang Yeon Hwang; Mi Kyeong Lee (PLoS ONE, 2017)
The composition and content of the active constituents and their biological activity vary according to diverse factors including their maturation stages. A previous study showed that the fruits of Cudrania tricuspidata inhibited pancreatic lipase activity, a key enzyme in fat absorption. In this study, we investigated the chemical composition and pancreatic lipase inhibitory activity of unripe and ripe fruits of C. tricuspidata. Unripe fruits of C. tricuspidata have a higher content of total phenolic and flavonoids and exhibited stronger pancreatic lipase inhibition compared to ripe fruits. HPLC analysis revealed the different chemical compositions of the unripe and ripe fruits. Further fractionation resulted in the isolation of 30 compounds including two new isoflavonoids. Analysis of the chemical constituents of the unripe and ripe fruits revealed that a 2,2-dimethylpyran ring, a cyclized prenyl, was the predominant side chain in the unripe fruits, whereas it was a linear prenyl group in the ripe fruits. In addition, a new isoflavonoid (19) from the unripe fruits showed the most potent inhibition on pancreatic lipase. Taken together, the maturation stage is an important factor for maximum efficacy and that unripe fruits of C. tricuspidata are a good source of new bioactive constituents for the regulation of obesity.